2018
DOI: 10.1186/s40792-018-0547-8
|View full text |Cite
|
Sign up to set email alerts
|

A case of duodenal hemorrhage due to arteriovenous malformation around a serous cystic neoplasm

Abstract: BackgroundNo reports have so far described arteriovenous malformation (AVM) in the pancreas caused by a tumor. We herein report a case of pancreatoduodenectomy for a patient who developed duodenal hemorrhage due to AVM developed around serous cystic neoplasm (SCN) of the pancreas.Case presentationA 79-year-old man was referred to our hospital because of anemia (Hb 7.4 g/dl) and pancreatic head tumor. Computed tomography showed microcystic-type SCN, 87 mm in size, in the pancreatic head. Vascular hyperplasia ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 20 publications
0
8
0
Order By: Relevance
“…We identified relevant articles pertaining to Ph-AVM in the English literature available on the PubMed electronic database. In total, 73 cases of Ph-AVM, including our case, have been reported on PubMed from 1968 to 2019, based on searches using "pancreas", "head", and "arteriovenous malformation" as keywords [4,5,[12][13][14][15][16][17][18][19][20][21][22] (Table 1). Sixty-four cases involved men (87.7%) and nine involved women (12.3%).…”
Section: Discussionmentioning
confidence: 99%
“…We identified relevant articles pertaining to Ph-AVM in the English literature available on the PubMed electronic database. In total, 73 cases of Ph-AVM, including our case, have been reported on PubMed from 1968 to 2019, based on searches using "pancreas", "head", and "arteriovenous malformation" as keywords [4,5,[12][13][14][15][16][17][18][19][20][21][22] (Table 1). Sixty-four cases involved men (87.7%) and nine involved women (12.3%).…”
Section: Discussionmentioning
confidence: 99%
“…The aetiology is unclear. The proposed causes include congenital malformation and acquired causes such as trauma or inflammation 3 …”
Section: Figmentioning
confidence: 99%
“…Haemorrhagic complication of PCNs is very rare, with only a handful of cases reported in the literature. [7][8][9] Pancreatic serous cystic neoplasms are a wholly benign entity. Early studies suggested that serous cyst adenomas had low malignant potential however there is a growing body of evidence to support that serous cystadenomas are indeed the only PCNs that are benign.…”
Section: Diagnosis Of New Pcns Is Almost Always Incidentalmentioning
confidence: 99%